The participation of the people of Bukhara in the world maritime trade in the Middle Ages - Vohidova Yulduz Roziqovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article involves the participation of Bukhara people in the world maritime trade and their history in the Middle Ages.